(untitled) (Altre Modernità, 2009)
Taking the lead from Don DeLillo’s epic novel Underworld (1997) – with its overarching theme of “waste” functioning as its unifying metaphor and its picture of the American deserts turned into hazardous waste dumps or missile depots – this essay provides a close reading of the empty spaces of the Nevada desert, spaces that bear the mark left by the nuclear exploitation and the hazardous waste which have plagued Nevada since the Fifties. By linking the history of Nevada to the Cold War, and to the chemical legacy of those years, with its notions of “containment” and “weather control”, Scarpino argues that they be read as interwoven threads of the same discourse.